Respiratory Cilia as a Therapeutic Target of Phosphodiesterase Inhibitors - Joskova, Marta; Mokry, Juraj; Franova, Sona (Frontiers in Pharmacology, 2020)
Mucociliary clearance is an essential airway defense mechanism dependent predominantly on the proper ciliary function and mucus rheology. The crucial role of cilia is evident in a variety of respiratory diseases, as the ciliary dysfunction is associated with a progressive decline in lung function over time. The activity of cilia is under supervision of multiple physiological regulators, including second messengers. Their role is to enable a movement in coordinated metachronal waves at certain beat frequency. Ciliary function can be modulated by various stimuli, including agents from the group of beta2-agonists, cholinergic drugs, and adenosine triphosphate (ATP). They trigger cilia to move faster in response to elevated cytoplasmic Ca2+ originated from intracellular sources or replenished from extracellular space. Well-known cilia-stimulatory effect of Ca2+ ions can be abolished or even reversed by modulating the phosphodiesterase (PDE)-mediated breakdown of cyclic adenosine monophosphate (cAMP) since the overall change in ciliary beating has been dependent on the balance between Ca2+ions and cAMP. Moreover, in chronic respiratory diseases, high ATP levels may contribute to cAMP hydrolysis and thus to a decrease in the ciliary beat frequency (CBF). The role of PDE inhibitors in airway cilia-driven transport may help in prevention of progressive loss of pulmonary function often observed despite current therapy. Furthermore, administration of selective PDE inhibitors by inhalation lowers the risk of their systemic effects. Based on this review we may conclude that selective (PDE1, PDE4) or dual PDE inhibitors (PDE3/4) increase the intracellular level of cyclic nucleotides in airway epithelial cells and thus may be an important target in the development of new inhaled mucokinetic agents. Further research is required to provide evidence of their effectiveness and feasibility regarding their cilia-modulating properties.